Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Lv, Di; Liu, Hongyun; An, Qi; Lei, Chengwei; Wang, Yanxuan; Sun, Jin; Li, Chuanhai; Lin, Yongfeng; Dong, Qing; Yang, Zhugen; Che, Kui; Liu, Wendong; et al. (Elsevier, 2024)
Hexafluoropropylene oxide dimer acid (HFPO-DA), known as “GenX” for its trade name, is gradually taking the place of Perfluorooctanoic acid (PFOA). However, there is a poor understanding of the developmental effects of GenX. This study aims to explore whether GenX produces adverse effects on offspring development in Sprague-Dawley (SD) rats and the underlying mechanisms. Pregnant rats were orally administered with GenX (0, 1, 10 and 100 mg/kg/day) from gestational 0.5–19.5 days. Experimental data showed that the exposure to GenX resulted in increased rats’ gestational weight gain, whereas both body weight and body length of their fetuses born naturally were significantly reduced. This could contribute to the developmental delays of fetal body weight, body length and tail length from postnatal 1–21 days. Histopathological evaluation of placenta indicated that GenX exposure led to neutrophil infiltration in decidual zone and congestion in labyrinth zone. Moreover, placental proteomics showed changes at the expression levels of the inflammation-related proteins in the Rap1 signaling pathway. In conclusion, gestational exposure to GenX induced fetal intrauterine and extrauterine development retardation in SD rats. Placental inflammation may play a key role in this process through the Rap1 signaling pathway.
Keywords: HFPO-DA (GenX); Developmental toxicity; Placenta; Rap1 signaling pathway